2002
DOI: 10.1007/s00213-002-1196-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective inactivation of the dorsomedial prefrontal cortex and the basolateral amygdala attenuates conditioned-cued reinstatement of extinguished cocaine-seeking behavior in rats

Abstract: TTX inactivation of the BLA, ACing, or PL impaired the ability of LT presentations to reinstate extinguished lever pressing for cocaine-paired stimuli. In contrast, inactivation of the IL or the S1BF had no effect on conditioned-cued reinstatement. Furthermore, there was no effect of TTX in any of the tested brain regions on general locomotor activity. CONCLUSIONS. These results support a role for the dorsomedial PFC and the BLA in the circuitry that mediates drug-seeking behavior elicited by cocaine-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
350
3
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(379 citation statements)
references
References 61 publications
25
350
3
1
Order By: Relevance
“…Thus, subjects can be used as their own controls. Using an infusion protocol and coordinates identical to those utilized in the present experiments, we have been able to establish functional dissociation between the dmPFC and vmPFC (McLaughlin and See, 2003), as well as between the BLA and the SSbf (McLaughlin and See, 2003) and central nucleus of the amygdala , suggesting that TTX administration resulted in selective inactivation of the target structures in the present study.…”
Section: Intracranial Infusionsmentioning
confidence: 55%
See 3 more Smart Citations
“…Thus, subjects can be used as their own controls. Using an infusion protocol and coordinates identical to those utilized in the present experiments, we have been able to establish functional dissociation between the dmPFC and vmPFC (McLaughlin and See, 2003), as well as between the BLA and the SSbf (McLaughlin and See, 2003) and central nucleus of the amygdala , suggesting that TTX administration resulted in selective inactivation of the target structures in the present study.…”
Section: Intracranial Infusionsmentioning
confidence: 55%
“…Studies from our laboratory (McLaughlin and See, 2003) have demonstrated that TTX microinfusions into the BLA do not significantly alter general activity during a 1-h locomotor activity test, suggesting that general motor deficits do not account for the effects of BLA inactivation on reinstatement. To further assess possible motor impairing effects of intracranial TTX infusions, we examined the effects of TTX infused into the dmPFC, DH, vmPFC, SStr, or SSbf on general activity.…”
Section: Contextual Reinstatement Testmentioning
confidence: 88%
See 2 more Smart Citations
“…Prefrontal cortical and limbic regions are also activated by nicotine-and cocaineassociated cues in rats, as measured by increased gene expression and dopamine release (Schroeder et al, 2001;Ito et al, 2000;Ciccocioppo et al, 2001;Phillips et al, 2003). Lesions of the basolateral amygdala or the prefrontal cortex disrupted responding maintained by cocaine-associated cues (McLaughlin and See, 2003). Intrabasolateral amygdala injections of SCH23390 blocked cue-induced reinstatement of cocaine seeking (See et al, 2001).…”
Section: Discussionmentioning
confidence: 99%